Perbandingan cadangan listrik dan hilang panas alamiah pada manifestasi mata air panas di daerah kawah timur gunung ambang dan daerah panas bumi lahendong - Palilingan, Rolles Nixon; Tumimomor, Farly Reynold; Mumek, Christofel Meidy (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. North Sulawesi is an area that has the potential for geothermal energy sources, characterized by the manifestation of hot springs, active volcanoes with temperatures ranging from 80-200 0C, one of which is in the eastern crater of Mount Amabang and the geothermal area of Lahendong. This research was conducted to calculate and determine the amount of natural heat loss (Heatloss) and electricity reserves from the manifestation of hot springs in the eastern crater of the threshold volcano and Lahendong geothermal area, also to find out the similarities and differences of these manifestations. The method used is direct observation and measurement in the field by measuring the parameters needed in this study. Based on the results of the study, the large natural heat dissipation from the manifestation of hot springs in the eastern crater of the threshold volcano by 0.1047 MW and the geothermal area of Lahendong by 0.0690 MW with electricity reserves in the eastern crater of the threshold mountain by 1,047 MW and the Geothermal Lahendong area amounting to 0.690 MW.Â Keywords: Threshold, Lahendong, heat loss, electricity.